Tantangan Perkembangan Usaha Pasar Tradisional: Studi pada Pasar Daerah Turen Kabupaten Malang - Fredy Ardiansyah; Suyeno; Langgeng Rahmatulllah Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Traditional markets are one of the economic infrastructure of cities/districts because of their role in contributing as cultural and social centers of society. The market is the center of various community activities for micro, small and medium enterprises whose development is very slow. Besides that, traditional markets are owned by the Regional Government and must continue to maintain and develop their existence so that they can grow well and compete with private markets or modern retail. There is a need for synergy between traditional and modern in order to provide the widest possible benefits to the prosperity of society and together build a better regional economy. This research is field research in the form of a case study located in Malang Regency with the research object being the Turen Regional Market Management Unit. The research method used is a qualitative method, while data was obtained from observations, interviews and documentation studies from related sources. This article attempts to describe and discover the factors that encourage and hinder the development of traditional market businesses in the era of economic globalization and the growth of modern markets.